127 Thermal Dynamics, Volumetrics and Seizure Outcomes Following Magnetic Resonance-Guided Laser Interstitial Thermal Therapy in Pediatric Lesional Epilepsy. Issue Volume 65:Issue CN(2018)Supplement 1 (16th August 2018) - Cobourn, Kelsey D; Fayed, Islam; Sullivan, Shannon; Oluigbo, Chima
Abstract: INTRODUCTION: Magnetic resonance-guided laser interstitial thermal therapy (MRgLITT) has emerged as a safe and effective minimally invasive technique for several intracranial pathologies. However, the effects of variable thermal energy on tissue ablation dynamics are poorly understood, particularly in the pediatric population. This study aims to examine the relationship between energy and volume of ablation in children undergoing MRgLITT for drug-resistant lesional epilepsy, define any correlation between volume ablated and seizure control outcome, and any disparities between underlying epileptogenic pathological substrates. METHODS: Single-center retrospective review of lesional epilepsy patients undergoing MRgLITT was performed. Volumes were measured by 2 raters using postablation T1-weighted MRI in Osirix. Inter-rater variability was analyzed via ANOVA. Linear regression analysis was performed to determine the relationship of energy to ablated volume. Fisher's exact test was used to assess independence of seizure outcome by Engel Scale from pathological substrate or ablated volume >1.5 cm 3 . RESULTS: Thirteen patients had twenty total lesions ablated. Substrates included tuberous sclerosis, focal cortical dysplasia, hypothalamic hamartomas, periventricular nodular hyperplasia, and mesial temporal sclerosis. Outcomes were documented to mean follow-up of 10 mo. Postoperative seizure control outcome was Engel-I in 9 (69.2%), Engel-II in 2 (15.4%), and Engel-III in 2 (15.4%) patients. Linear regression was calculated to predict the effect of energy on volume of ablation ( P = 6.47E-6, R = 0.841). Linear correlation between energy and volume was found to be strongest in tuberous sclerosis lesions (R = 0.88) and weakest in cortical dysplasia (R = 0.057). Inter-rater differences were insignificant ( P = .73). There was no significant relationship between pathological substrate or volume of ablation >1.5 cm 3 and seizure control by Fisher's exact test ( P = .67; P = .73). CONCLUSION: We characterized a linear relationship between the in vivo application of thermal energy and ablated volume. The strength of this correlation was variable across different substrates, but pathological substrate did not predict seizure outcome. More study is needed in larger populations before these relationships can be fully understood.